2012
DOI: 10.1371/journal.pone.0030091
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Patterns of Wikipedia Editorial Activity: A Demographic Analysis

Abstract: Wikipedia (WP) as a collaborative, dynamical system of humans is an appropriate subject of social studies. Each single action of the members of this society, i.e., editors, is well recorded and accessible. Using the cumulative data of 34 Wikipedias in different languages, we try to characterize and find the universalities and differences in temporal activity patterns of editors. Based on this data, we estimate the geographical distribution of editors for each WP in the globe. Furthermore we also clarify the di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
118
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(124 citation statements)
references
References 23 publications
5
118
0
1
Order By: Relevance
“…Almost all weekdays showed similar contribution patterns; only on Sundays did the project prove to have a slightly larger number of data edits, while the afternoon and evening hours were identified as time ranges with the highest activity in OSM for each day. Overall, the discussed results of the OSM project match similar patterns previously found in Wikipedia [128] or mobile phone communication behavior [129]. Neis and Zipf [71] also identified different member groups in OSM based on the number of contributions the members made to the project and revealed that only around 5% of all members contributed in a significant way.…”
Section: Participation Inequalitysupporting
confidence: 78%
“…Almost all weekdays showed similar contribution patterns; only on Sundays did the project prove to have a slightly larger number of data edits, while the afternoon and evening hours were identified as time ranges with the highest activity in OSM for each day. Overall, the discussed results of the OSM project match similar patterns previously found in Wikipedia [128] or mobile phone communication behavior [129]. Neis and Zipf [71] also identified different member groups in OSM based on the number of contributions the members made to the project and revealed that only around 5% of all members contributed in a significant way.…”
Section: Participation Inequalitysupporting
confidence: 78%
“…The activity shows a slight increase until around 9 p.m., where it start to decrease during night. This result corresponds closely to the circadian patterns previously observed in Wikipedia [26] as well as qualitatively corresponding to the other kind of human activities such as mobile calling behaviour [11], and the Internet instant messaging [18]. However, Rome editors show more activity around noon and less in the afternoon compared to London editors.…”
Section: Resultssupporting
confidence: 87%
“…While early analyses primarily investigated the quality of the outcome, over the last years the activity of VGI communities itself has come into focus. While activity of online communities has been studied in different domains, e.g., in the context of Wikipedia [2,3], VGI projects such as OpenStreetMap (OSM) are a welcome playground for GI scientists due to their open access policies and well-documented community processes, e.g., mailing lists or the OSM Wiki. Moreover, the OSM project maintains a complete history of the database back to the year 2005.…”
Section: Introductionmentioning
confidence: 99%